Labor market impacts of a large-scale public works program: Evidence from the Indian Employment Guarantee Scheme - Laura Zimmermann (Institute for the Study of Labor (IZA), 2012)
Recent years have seen an increasing interest in using public-works programs as anti-poverty measures in developing countries. This paper analyzes the rural labor market impacts of the Indian National Rural Employment Guarantee Scheme, one of the most ambitious programs of its kind, by using a regression discontinuity design. I find that private-sector wages increase substantially for women, but not for men, and that these effects are concentrated during the main agricultural season. In contrast, there is little evidence for negative private employment effects.
Keywords: H53; I38; J22; J23; J38; 330; public works program; National Rural Employment Guarantee Scheme; NREGA; NREGS; India; regression discontinuity design; Arbeitsbeschaffung; Wirkungsanalyse; Ländlicher Arbeitsmarkt; Fraueneinkommen; Indien